What do they think of "chemistry-enviro"? / Sharipah Ruzaina Syed Aris, Zuraidah Abdullah Munir and Zurina Shaameri - Syed Aris, Sharipah Ruzaina; Abdullah Munir, Zuraidah; Shaameri, Zurina (2002)
Recently, a large number of researchers examines students' misconceptions, students' understanding on chemistry concepts and not to forget teaching methods that are appropriate to the students in order to enhance meaningful learning, thus improve students' achievement. Somehow they forgot to appreciate the powerful impact of emotions or feelings that students would face in the process of learning. By considering this factor, we have decided to find out what Engineering students think of "chemistry enviro ". Meaning, the chemistry subject itself and the lecturers' teaching style. in this study, we try to elicit the Engineering students (N=62) feeling about chemistry. What is the most difficult topic in CHM 140 syllabus? Why do they think the subject is difficult? Do they like their lecturers' teaching style? Anecdote of the findings, transition metal is the most difficult topic, followed by quantum mechanics, electrochemistry and acid-base. Most students found the topics difficult because they involved too many calculations and memorization. From this survey we also found that 43.2% of the lecturers applied two-way interaction and created learning-active environment during their classes. The study also revealed that more than 80% of the students enjoyed their chemistry classes.